Religious affiliation and child mortality in Ireland: A country-wide analysis based on the 1911 census - Lucia Pozzi; Francesco Scalone; Michail Raftakis; Liam Kennedy (Queen's University Centre for Economic History (QUCEH), 2024)
Previous studies have identified a link between religious affiliation and child mortality, yet the underlying factors that contributed to this association are not fully understood. This study investigates how religious affiliation might have influenced child mortality in early 20th- century Ireland, having controlled for socio-economic status, literacy, and place of residence at both individual and contextual levels. We utilize the 1911 IPUMS Irish census, indirect techniques, and regression analysis to examine the role of religious affiliation on child mortality. We conduct various OLS regressions, controlling for demographic factors and socioeconomic conditions at both individual and contextual levels. Our results indicate striking differences in child mortality rates among the three major religious denominations in Ireland in the early twentieth century. Catholics recorded the highest child mortality rates, followed by Church of Ireland families, while Presbyterians experienced the best child mortality outcomes. These differences are explained in part by the varying socioeconomic characteristics of each religious group but religious affiliation is also shown to have mattered. For reasons that are not altogether clear, Jewish communities (to compare one of the smaller religious denominations) had lower child mortality rates than any the three major religious denominations.
Keywords: 330